2012
DOI: 10.1136/annrheumdis-2011-200987
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping and conditional analysis identify a new mutation in the autoimmunity susceptibility gene BLK that leads to reduced half-life of the BLK protein

Abstract: ObjectivesTo perform fi ne mapping of the autoimmunity susceptibility gene BLK and identify functional variants involved in systemic lupus erythematosus (SLE). Methods Genotyping of 1163 European SLE patients and 1482 controls and imputation were performed covering the BLK gene with 158 single-nucleotide polymorphisms. Logistic regression analysis was done using PLINK and conditional analyses using GENABEL's test score. Transfections of BLK constructs on HEK293 cells containing the novel mutation or the wild t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…In this regard, few examples exist of rare genetic variants in SLE related to the genes identified in GWAS studies. One example is BLK, where a rare mutation (a nonsynonymous change from alanine to threonine) was identified [41]. We recently observed that such mutation could modify the protein-protein interaction of BLK with BANK1 through alteration of the SH3 domain of BLK [42].…”
Section: Key Pointsmentioning
confidence: 98%
“…In this regard, few examples exist of rare genetic variants in SLE related to the genes identified in GWAS studies. One example is BLK, where a rare mutation (a nonsynonymous change from alanine to threonine) was identified [41]. We recently observed that such mutation could modify the protein-protein interaction of BLK with BANK1 through alteration of the SH3 domain of BLK [42].…”
Section: Key Pointsmentioning
confidence: 98%
“…Reducing BLK levels in mouse pDC increased TLR9-induced IFNα production(105). Given that genetic variants in the BLK locus are identified in SLE patients by genome-wide association studies, it is notable that certain polymorphisms correlate with reduced BLK levels(106). Consequently, this may elevate IFNα secretion and hence contribute to SLE predisposition.…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…BLK is also associated with other autoimmune disorders, such as rheumatoid arthritis (RA) (6), systemic sclerosis (SSc) (7), Sjögren’s syndrome (8, 9), primary anti-phospholipid syndrome (APS) (10), dermatomyositis (11) and Kawasaki disease (12). The SNP risk alleles found in regulatory regions have been shown to associate with reduced mRNA levels of BLK and reduced protein expression (3, 1315). …”
Section: Introductionmentioning
confidence: 99%
“…BLK is mainly expressed by B lymphocytes but also, to a lesser extent by non-B-cell lineages, such as plasmacytoid dendritic cells (pDCs), pancreatic β-cells, and γδT cells (13, 1619). Though Blk phosphorylation is detectable upon anti-IgM stimulation (2022), BLK expression is downregulated upon BCR stimulation (15), suggesting that BLK may play a dual role downstream of BCR signaling.…”
Section: Introductionmentioning
confidence: 99%